2019
DOI: 10.1016/j.clinthera.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Components of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome Uncover Potential Transposable Element Activation

Abstract: Purpose: Studies to determine epigenetic changes associated with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) remain scarce; however, current evidence clearly shows that methylation patterns of genomic DNA and noncoding RNA profiles of immune cells differ between patients and healthy subjects, suggesting an active role of these epigenetic mechanisms in the disease. The present study compares and contrasts the available ME/CFS epigenetic data in an effort to evidence overlapping pathways capable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 129 publications
6
18
0
Order By: Relevance
“…As previously published by our group, it seems possible that the activation of particular patterns of transposable elements (TEs) associating with ME/CFS epigenetic marks may trigger ME/CFS patient flu-like symptoms in the absence of concomitant active infections [34]. Further work after this publication by Dr. Romano s group at the Universidade de Sao Paulo in Brazil, in fact supports that the levels of the endogenous retrovirus HERV-K are upregulated in ME/CFS.…”
Section: Introductionsupporting
confidence: 67%
“…As previously published by our group, it seems possible that the activation of particular patterns of transposable elements (TEs) associating with ME/CFS epigenetic marks may trigger ME/CFS patient flu-like symptoms in the absence of concomitant active infections [34]. Further work after this publication by Dr. Romano s group at the Universidade de Sao Paulo in Brazil, in fact supports that the levels of the endogenous retrovirus HERV-K are upregulated in ME/CFS.…”
Section: Introductionsupporting
confidence: 67%
“…Recently, it was suggested that differential methylation patterns of promoters in ME/CFS would impact on the expression of nearby transposable elements, including HERVs [19]. Two reports of HERV activity in ME/CFS were published some years ago but the results were conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the activated "cut and paste" TEs will not be retrotranscribed due to failure of fragmented tRNAs (tsRNAs) to prime [52], preserving genome integrity under a normalscenario (Figure 4). It is therefore hypothesized that an increase in long dsRNA intracellular levels in FM and ME/CFS patients deriving from epigenetic changes, as described [20][21][22][23][24][25][26][27][28][29][30][31]34], could in fact constitute a trigger for the disease in the absence of viral or other type of infection. It is perhaps the particular type of activated elements what drives the individual phenotype towards autoimmunity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As published, we uncovered particular patterns of transposable elements (TEs) associating with ME/CFS epigenetic marks leading to the interesting possibility that it is the activation of dormant TEs that may trigger ME/CFS patient flu-like symptoms in the absence of concomitant active infections [ 34]. Since then, the group led by Dr. Romano at the Universidade de Sao Paulo in Brazil, have informed that the levels of the endogenous retrovirus HERV-K appear in fact upregulated in ME/CFS, as shown by the analysis of PBMCs isolated from ME/CFS patients at the monographic UK ME biobank [35], supporting the hypothesis raised by our group [34]. However, and although FM frequently presents comorbid ME/CFS syndrome, no study has yet determined whether patients with a diagnosis of FM presents similar activation of this group of TEs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation